Gamification as a tool for learning and assessment of soft skills at school - Natalia Altomari; Antonella Valenti (Formare, 2023)
Learning and assessing new skills is a challenge in education that teachers must take up primarily, playing a key role in the educational success of each student. With this perspective, soft skills (or transversal skills) are often considered of secondary importance, instead, if developed properly, they are among the skills required in the world of work, as well as in the purely educational world. Such skills, activated and enhanced through an innovative tool such as gamification, could be an answer to this gap. Serious games, in fact, are not only a means of entertainment or playfulness but are increasingly finding their place in the educational field.